Hubungan antara Kematangan Emosi dan Dukungan Sosial terhadap Konflik Interpersonal Peserta Didik SMA - Dwi Emilia Rosanti; Denok Setiawati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the relationship between emotional maturity and social support with interpersonal conflict among tenth-grade students at SMA Wachid Hasyim 5 Surabaya. Employing a quantitative approach with a correlational design, the research involved 68 respondents selected through purposive sampling, using validated and reliable instruments measuring emotional maturity, social support, and interpersonal conflict. The findings reveal that emotional maturity has a negative and significant relationship with interpersonal conflict (r = -0.395; p = 0.001), indicating that students with higher emotional maturity tend to experience fewer conflicts. Social support also shows a negative and significant relationship with interpersonal conflict (r = -0.316; p = 0.009), suggesting that greater support from the surrounding environment contributes to lower levels of conflict. Multiple regression analysis further demonstrates that both variables simultaneously exert a significant influence on interpersonal conflict, with an F-value of 9.079 and an R Square of 0.218, meaning that 21.8% of the variance in interpersonal conflict can be explained by emotional maturity and social support. These results highlight the importance of strengthening emotional skills and enhancing social support systems to foster more positive and harmonious social interactions in the school environment.